The role of nanomaterials and antibiotics in microbial resistance and environmental impact: an overview. (September 2021) - Herrera, Genesis; Peña-Bahamonde, Janire; Paudel, Sachin; Rodrigues, Debora F
Highlights: Overview of recent NDDS for drug delivery applications. Mechanisms of action of known and common nanoparticle and antibiotics. Nanoparticle microbial resistance and potential adverse effects. Impacts of nanoparticle and antibiotics combinatorial treatments in the environment. Abstract : Increasing interest in the combinatory effects of nanoparticles (NPs) and antibiotics to diminish antibiotic resistance emergence, while maintaining antimicrobial properties, have grown over the years. Furthermore, diverse compounds used to synthesize nanoparticles have enhanced drug delivery, stability, efficiency, and reactivity. Nevertheless, nanotechnology, in the medical and veterinary fields, is minimally introduced despite preventing antibiotic resistance and its microbicidal activity. This cautious clinical introduction of antibiotic-nanoparticles for drug delivery is appropriate because the long-term human, animal, and environmental effects of nanomaterials remain unknown. Furthermore, there is a lack of understanding about the effects of biological processes from antibiotic-nanoparticle combinatorial treatments. Hence, to avoid another antibiotic resistance crisis, further investigation and clinical introduction caution is needed to determine the effects of synthesis and applications on combinatory treatments.